Synthesis, crystal structure and Hirshfeld surface analysis of ethyl 4-hydroxy-2-(4-hydroxyphenyl)-1-methyl-5-oxo-2,5-dihydro- 1H-pyrrole-3-carboxylate - Fatin Nur Ain, Abdul Rashid; Siti Syaida, Syaida Sirat; Husna Izzati, Muhammad Nor Azharan; Muhamad Zulfaqar, Bacho; Slawin, Alexandra M.Z.; Mohd Fazli, Mohammat; Mohd Fadhlizil Fasihi, Mohd Aluwi; Nor Saliyana, Jumali; Mohd Abdul Fatah, Abdul Manan (Elsevier B.V., 2023)
Ethyl 4 hydroxy-2-(4-hydroxyphenyl)-1-methyl-5-oxo-2,5-dihydro-1H-pyrrole-3-carboxylate, C14H15NO5 (1) was synthesized via multicomponent reaction (MCR) of sodium diethyl oxalacetate, methylamine, and 4-hydroxybenzaldehyde. The structure of 1 was elucidated by using FT-IR, NMR and GCMS. These results were further confirmed by means of single crystal X-ray crystallography. The results showed that 1 was crystallized in orthorhombic space group Pca21 where a = 17.102(4), b = 9.923(2), c = 16.037(4), Å. The quantification of intermolecular interactions in the crystal structure was obtained by Hirshfeld surface analysis and showed that the H•••H contacts were the most dominant interactions.